2014
DOI: 10.1590/s0102-33062014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Tree community dynamics in a submontane forest in southeastern Brazil: growth, recruitment, mortality and changes in species composition over a seven-year period

Abstract: In order to assess long-term community dynamics in tree populations, we investigated trees with a diameter at breast height (DBH) ≥ 5 cm in an 11-ha fragment of submontane tropical forest in southeastern Brazil, at the beginning and end of a seven-year period. We observed a general tendency toward decreasing numbers of trees and toward stability in basal area. The stability in basal area was associated with an equilibrium between the loss of trees and the basal area gain from the horizontal growth of surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This result is consistent with previous studies 33 34 . This suggests demographic shifts in some species populations, which, due to low number of recruits, have trouble surviving in the community 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous studies 33 34 . This suggests demographic shifts in some species populations, which, due to low number of recruits, have trouble surviving in the community 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the forest is at an earlier stage of succession. The pace of forest dynamics is the result of numerous factors, including topography, geology and climate, organisms present and the stage of succession, as well as anthropogenic factors in lands surrounding the reserve 35 . Of these, topography most distinguishes Dinghushan plot from the other forest dynamics plots.…”
Section: Discussionmentioning
confidence: 99%
“…These results do not support assumptions of greater species richness with increased area and lower species richness with increased isolation. This enhances the factor disturbance, revealed at various levels in the remnants, as a strong influence in variation of composition and species richness of these remnants (Pessoa & Araujo 2014), and also calls attention to the importance of interaction between factors. In fact, species composition by functional group and by dispersal syndrome revealed that the remnants still allow the presence of high proportion of large-seeded species associated with frugivores (Santos et al 2008).…”
Section: Remnant Attributes and Variations On Species Richness And Compositionmentioning
confidence: 95%
“…In the Brazilian Atlantic Forest, the landscape has been modified by various activities for over two centuries. In recent decades, forests that lie at low elevations on the so-called "sea of hills" in the central part of Rio de Janeiro state have been devastated mainly by cattle-raising activities (Carvalho et al 2006;Pessoa & Araujo 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it enables the formation of genetic reservoirs, increases forest yield and health, and plays a key role in tree species' functioning. Diversity allows species to evolve during periods of extensive genetic change, based on their adaptation to different climate regimes (RATNAM et al, 2014;FAO, 2014). Genetic material also enables forest resilience and survival after anthropogenic disturbances (STEFFEN et al, 2015).…”
Section: Genetic Conservationmentioning
confidence: 99%